Efficient machinery selection for agricultural operations in a plantation. - Bardaei, M. Zohadie; Wan Ismail, Wan Ishak
The application of machines to agricultural production has been one of the outstanding development in Malaysian agriculture during the past decades. Proper selection and use of agricultural machinery could have a significant effect in accelerating the agricultural development in Malaysia. The purpose of this paper is to present an analytical procedure which could be used by a plantation manager for the problem of selecting agricultural equipment. The economic selection of filed equipment has the advantages of more efficient power use,labour savings,greater timeliness for critical operations,reduction of production costs,improved quality and also encourages better management. The procedure presented can be used to determine the optimum economic size for field implement. The concept in the procedure is first to determine the total annual cost of using the implement as a function of its size. The optimum size is then determined by obtaining the minimum cost point through differentiation. An example for a hypothetical situation is also presented to illustrate the use of the procedure.